2015
DOI: 10.4103/1947-2714.159332
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of group versus individual yoga exercises on fatigue of patients with multiple sclerosis

Abstract: Background:Multiple sclerosis disorders poses heavy physical and emotional effect on patients who are associated with the disease.Aim:This study aimed to compare the effectiveness of individual versus group exercises on fatigue on patients with multiple sclerosis.Materials and Methods:In this clinical trial, 85 patients with multiple sclerosis were divided in two groups of individualized exercise and team exercise. The intervention was conducted for 6 weeks and comprised of mild stretching and basic yoga exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Note: Studies that were included in the review but not mentioned in the main text are the following . 76 …”
Section: Discussionmentioning
confidence: 99%
“…Note: Studies that were included in the review but not mentioned in the main text are the following . 76 …”
Section: Discussionmentioning
confidence: 99%
“…With exercise, some studies suggest that synergistic effects can be observed if exercises are performed in group settings [ 28 ]. On the other hand, there appears to be no evidence of difference in the self-reported benefits that can be derived from performing yoga alone versus in a group setting [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, cancer centers can offer MBME classes at a relatively low cost (Karbandi, Gorji, Mazloum, Norian, & Aghaei, 2015). Classes usually require relatively little space and an instructor who can guide about 20 participants (Herman, 2013).…”
Section: Mind-body Movement Exercise Classesmentioning
confidence: 99%